BOTULINUM TOXIN TYPE A (BoNT-A) FOR NEUROPATIC CANCER PAIN : A SYSTEMATIC REVIEW - Christy; Alvionita Muntholib (International Medical Journal Corp. Ltd, 2026)
Background: Neuropathic cancer pain (NCP) is a highly prevalent and debilitating condition affecting 30–50% of cancer patients undergoing treatment, with rates rising to 70–90% in advanced stages. Conventional pharmacotherapy, including opioids and adjuvants, often provides inadequate relief or causes significant adverse effects, highlighting the need for alternative therapeutic strategies. Botulinum Toxin Type A (BoNT-A) has emerged as a potential analgesic agent with a unique mechanism of action. Objective: To systematically evaluate the effectiveness and safety of BoNT-A as a therapeutic option for neuropathic cancer pain. Methods: A systematic review was conducted following PRISMA 2020 guidelines. Four databases (PubMed, ScienceDirect, Cochrane Library, ProQuest) were searched for randomized controlled trials (RCTs), pilot studies, and prospective cohort studies published between January 2015 and January 2025. Inclusion criteria were: studies assessing BoNT-A for NCP, quantitative pain outcomes, English language, and sample size ≥10 patients. Results: Six studies (five RCTs and one prospective open-label study) involving 151 cancer patients were included. All studies reported statistically significant pain reduction following BoNT-A injection, with pain scores decreasing by 30–50% in most trials. Functional outcomes, such as arm mobility and quality of life, also improved. BoNT-A demonstrated a favorable safety profile, with only mild, transient local side effects. No serious systemic adverse events were reported. Discussion: BoNT-A reduces NCP through multiple mechanisms: inhibition of acetylcholine, substance P, CGRP, and glutamate release; modulation of TRPV1 receptors; and central antinociceptive effects. Evidence supports its role as an effective adjunct or alternative to opioids, particularly in post-surgical and post-radiotherapy pain. Conclusion: BoNT-A is effective and safe for managing neuropathic cancer pain. Further large-scale RCTs are needed to establish optimal dosing, long-term efficacy, and comparative effectiveness against standard therapies.